The effect of the educational technological workshop strategy on learning technical performance and accuracy of tennis skills for under 20 years of age - Tahseen, Tahseen Husni (International Journal of Psychosocial Rehabilitation, 2020)
The educational technological workshop process has an effective role for the trainer that helps him in delivering the basic skills of the game to the player, and through field visits made by the researcher to the specialized school to take care of talent, it became necessary to introduce new educational auxiliary methods such as using the educational workshop with a technology of superior tennis skills You need great control during learning and motor performance, through which the basic skills to be learned are explained and clarified, and immediate feedback is provided that would enhance the information for the learner, and the research aims to prepare an educational technological workshop strategy in learning the technical performance and accuracy of tennis skills The ground is under 20 years old, and the researcher used the experimental approach in the pre and post testing of the two experimental and control groups for its suitability to the nature of the research. The search was by the method of comprehensive inventory and the sample was divided into two groups, the experimental and the control group, with ( Six players) for each group. The educational technological workshop strategy was applied for a period of eight weeks, with three training units per week. The researcher used the statistical bag (spss) to process the data and the researcher reached the most important conclusions. There is a positive effect of the educational technological workshop strategy on learning the technical performance and accuracy of tennis skills. Under 20 years old.